Light Non-Aqueous Phase Liquid (Lnapl) Vertical And Lateral Migration Behaviour Due To Fluctuating Groundwater Table - Lee, Yip Yong (Universiti Sains Malaysia, 2021)
Migration behaviour of Light Non-Aqueous Phase Liquid (LNAPL) is complex depending on different subsurface environment. For better remediation efficiency, 2D tank experiments were conducted to study effect of the groundwater fluctuation on the lateral and vertical migration behaviour of LNAPL. The porous media used was poorly graded and has good drainage properties. Simplified Image Analysis Method (SIAM) was adopted to access saturation distribution of LNAPL and water in the domain of 2D water tank with two types of groundwater fluctuation (wet / dry season) and two volumes of LNAPL released. Water level first raise then drop for wet season scenario while opposite sequence for dry season scenario. In wet season scenario and low volume scenario, LNAPL saturation at the raised water level first increased then dropped to 20 %. No sign of LNAPL found at initial water level due to high capillary force. At 20 cm to the right of releasing source, final reaching LNAPL saturation increased to 15 % signified LNAPL lateral movement. In dry season scenario, LNAPL saturation at lowermost water level remained zero. LNAPL saturation at initial level increased to 16 % and fall to 11 % after displaced by capillary force due to raising water, thereafter entrapped immobile LNAPL below saturated zone. Consistent surge of LNAPL saturation to 13 % observed due to lateral movement. In comparison, LNAPL in dry season has greater penetration depth and radial displacement because of high infiltration and spreading rate induced by lowering of water tables. Double volume of LNAPL under these two groundwater fluctuations show similar vertical and lateral migration behaviour except that there would be higher LNAPL saturation deposited at each study location, greater penetration depth and radial displacement compared to the corresponding applied scenario. Overall, SIAM shows its effectiveness to evaluate saturation distribution of LNAPL and water in two-dimensional scale.